PENGARUH KADAR PEREKAT DAN CAMPURAN KULIT TERHADAP SIFAT FISIS DAN MEKANIS PAPAN PARTIKEL TUSAM (Pinus merkusii) - I M Sulastiningsih; Rozak Memed; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
The  laboratory   test  of  strength  properties   of pine  particleboard subtituted  with 0,  20, 40 and 60 percent of pine bark, glued  with  8, 10, and  12 percent   liquid  urea formaldehvde    (by particle  dry  weight  basis) is reported   in  this paper.  Pine  wood  and  its  bark  were obtained   from West Java.                                                                                                                                                    The result  shows  that  the substitution with  bark of  20,  40,  and  60 percent   of pine   wood  particle  improved   water absorption   and  thickness- swelling  properties;   however,  it decreased  mechanical properties of particleboard.  Particleboard with  high  bark  content   has lower  mechanical  properties   than  that  with  low  bark content.   The physical   and  mechanical properties   of  particleboard   that  is subtiuuted  with  20 and  40%  bark and  10 and  12%  urea-formaldehyde resin meet the FAO   standard   for   medium   density   particleboard,  except for,  modulus of rupture. If   we  compared  with  Indonesian standard,  the properties  that do not  meet  the standard  are the modulus  of rupture  and the internal  bond strength